Improving the flexural property and long-lasting anti-ablation performance of the CVD-HfC coating by in-situ growing HfC nanowires. Issue 18 (15th December 2019) - Ren, Jincui; Zhang, Yulei; Zhang, Jian; Fu, Yanqin
Abstract: HfC nanowires (HfCNWs) were in-situ synthesized via CVD technique and acted as the reinforcement in the CVD-HfC coating for C/C composites. The morphology, flexural property and long-lasting anti-ablation performance of the HfC coating were researched. The deposition efficiency and compactness of the HfC coating were both elevated by virtue of in-situ growing HfCNWs. The flexural property of the coated C/C exhibited a pronounced increment on account of incorporating HfCNWs. HfCNWs formed an interlocking network in the oxide layer and inhibited the coating delamination or spalling in harsh ablation condition, so the long-lasting anti-ablation performance of the HfCNWs-reinforced HfC coating improved. After exposure to the oxyacetylene flame for 120 s, the mass and linear ablation rates of the HfCNWs-HfC-coated C/C were only 0.57 mg/s and -0.35 μm/s, which were 54.03% and 117.77% reduction in comparison with those of the HfC-coated C/C (1.24 mg/s and 1.97 μm/s).